ICT Utilization in Science Teachers of Underdevelopment Region - Saefuddin Saefuddin; Saleh Saleh; Fahyuddin Fahyuddin (Universitas Pendidikan Ganesha, 2021)
Research has been carried out to examine the use and mastery of ICT for science teachers in underdeveloped areas. This study aims to: obtain valid data regarding teachers' ICT knowledge and skills; knowing the extent to which the teacher implements ICT knowledge and skills in the classroom; identify the factors faced by teachers in implementing ICT in learning; to determine support and effective ICT development strategies to be applied to teachers. The research method is a survey, practical test, and statistical validation. It found that male teachers, young teachers, honorary teachers, and secondary school teachers tended to have higher ICT competence. It was found that the ICT applications that have been used by more than 50% of teachers are word processing, presentation processing, internet, and document navigation. The analysis results show that only about 2% of teachers stated that ICTs had little effect on their learning in the classroom and that training on how to do this had the most positive impact on teachers. It can be concluded that professional training on ICT needs to be effectively and sustainably provide; continuing to improve ICT infrastructure in schools will positively impact the use of ICT by teachers; teachers' overall attitude is very positive for self-development.